2017
DOI: 10.1111/jfpp.13209
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbial, antioxidant, and sensory properties of probiotic stirred yoghurt enriched with Aloe vera foliar gel

Abstract: The present study reports the physicochemical, textural profile, microbial, antioxidant, and sensory characteristics of the produced yoghurt containing Aloe vera foliar gel. The result showed that syneresis was increased gradually with increase in Aloe vera foliar gel concentration during storage period. Aloe vera leaf gel had a negative effect on L. Acidophilus and B. lactis Bb‐12, but the viable cells were in the acceptable range according to FAO (106−107 CFU g−1). The flow behavior for all yoghurt samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
(60 reference statements)
3
20
5
Order By: Relevance
“…The protein matrix had an important role in cohesiveness (Tunick, ). Our result is opposite to the findings obtained for yogurt containing Aloe Vera foliar gel that decrease in cohesiveness reported in the final product (Azari‐Anpar, Tehrani, et al., ; Azari‐Anpar, Payeinmahali, et al., ). Also, it was reported that the addition of 3.0%, 4.0%, and 5.0% of dried grape pomace into the yogurt samples reduced cohesiveness amounts (Mohamed, Zayan, & Shahein, ).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The protein matrix had an important role in cohesiveness (Tunick, ). Our result is opposite to the findings obtained for yogurt containing Aloe Vera foliar gel that decrease in cohesiveness reported in the final product (Azari‐Anpar, Tehrani, et al., ; Azari‐Anpar, Payeinmahali, et al., ). Also, it was reported that the addition of 3.0%, 4.0%, and 5.0% of dried grape pomace into the yogurt samples reduced cohesiveness amounts (Mohamed, Zayan, & Shahein, ).…”
Section: Resultscontrasting
confidence: 99%
“…(); Azari‐Anpar, Payeinmahali, et al. () that found the addition of gums caused enhancement in gumminess. These authors found there is an effective relationship between the fermentation velocity and gumminess (Azari‐Anpar, Tehrani, et al., ; Azari‐Anpar, Payeinmahali, et al., ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The titratable acidity during the storage period was measured by titration with 0.1N NaOH solution and phenolphthalein as the indicator according to Azari‐Anpar, Payeinmahali, Daraei Garmakhany, and Sadeghi Mahounak (). The apparent viscosity of set‐yoghurt samples was determined in programmable digital viscometer (Brookfield, model DV‐E, USA) based on measuring resistance to a rotating spindle as explained by Ranadheera, Evans, Adams, and Baines ().…”
Section: Methodsmentioning
confidence: 99%